The Old Testament library : Genesis : a commentary - Rad, Gerhard von, 1901-1971.; Marks, John H. (John Henry) (Philadelphia : Westminster Press, 1972)
This book makes available to English-speaking students a work that in the original German has achieved the status of a theological classic. This revised edition contains the extensive changes prepared by the author before his death. The introduction has been largely rewritten and the early chapters of the commentary have been reworked with equal thoroughness. Parts 1 and 2 have been entirely reset, and minor alterations have been made in part 3. Professor von Rad has utilized the results of literary criticism and form criticism in producing a commentary that is exegetical, historical, and above all, theological. In every phase of the panoramic pageant the reader sees the God of Israel reaffirming the terms of his covenant and working out his great historical purposes in spite of, and even through, the disobedient acts of willful, headstrong men. - Jacket flap.
Introduction -- The biblical primeval history -- The biblical patriarchal history.
Translation of Das erste Buch Mose: Genesis, v. 2-4 of Das Alte Testament deutsch. Text revised on the basis of the 9th German ed., 1972.
Includes bibliographical references.
Keywords: Bible. -- Commentaries